Single-Nucleotide Polymorphism of CYP3A5 Impacts the Exposure to Tacrolimus in Pediatric Renal Transplant Recipients: A Pharmacogenetic Substudy of the TWIST Trial - Billing, Heiko; Höcker, Britta; Fichtner, Alexander; van Damme-Lombaerts, Rita; Friman, Styrbjorn; Jaray, Jenö; Vondrak, Karel; Sarvary, Eniko; Dello Strologo, Luca; Oellerich, Michael; von Ahsen, Nicolas; Tönshoff, Burkhard (Therapeutic drug monitoring, 2017)
BACKGROUND: The pharmacokinetics of tacrolimus (TAC) and mycophenolic acid (MPA) are highly variable. An impact of single-nucleotide polymorphisms (SNPs) of the genes coding for enzymes and transporters involved in the pharmacokinetics of TAC and/or MPA is intuitively conceivable. Accordingly, we sought to analyze the influence of different SNPs on TAC and MPA exposure in pediatric renal transplant recipients. METHODS: A subpopulation of 37 patients (median age: 12.8 years, range 2.2-18.3 years) participating in the TWIST study was included in the analysis of SNPs of CYP3A5, ABCB1 (MDR1), ABCG2, SLCO1B3 (coding for OATP2), ABCC2 (coding for cMOAT), and UGT1/2. TAC trough concentrations and abbreviated area under the concentration-time curves (AUC) of MPA were measured on days 7, 28, 91, and 183 after transplant. Both of these were adjusted to the respective dose the patient received. RESULTS: The allele frequencies of analyzed SNP's were comparable to those reported previously for white populations. Dose-adjusted trough concentrations of TAC were approximately 60% lower in patients with the CYP3A5*1/*3 allele as compared with the CYP3A5*3/*3 allele (P = 0.004). Steroid-free patients in CYP3A5*3/*3 and CYP3A5*1/*3 carrier subgroups had comparable dose-adjusted TAC concentrations to the subgroup on steroids (P = 0.13). Patients younger than 10 years had a significantly lower median dose-adjusted TAC C0 concentration than patients older than 10 years; this age effect was comparable in heterozygous and homozygous CYP3A5 carriers as well as in patients on and off steroid medication. As for MPA, the genetic variability of transporters or enzymes had no impact on dose-adjusted MPA-AUC due to the low allele frequencies. Patients off steroids had a higher dose-adjusted MPA-AUC (0.18 mg·h/L per mg/m, 0.012-0.27) compared with patients on steroids (0.12 mg·h·L·mg, 0.09-0.19; P = 0.04). CONCLUSIONS: Genetic variability of CYP3A5 has an impact on TAC metabolism in pediatric renal transplant recipients, contributing partly to the variability of TAC exposure. Therefore, adjusting initial TAC dosing to the genotype of CYP3A5 might be of clinical benefit.
Keywords: Mycophenolic Acid; Pharmacogenetics; takrolimus; Tacrolimus; alely; Kidney Transplantation; předškolní dítě; imunosupresiva; Humans; farmakogenetika; Gene Frequency; Genotype; transplantace ledvin; Time Factors; mužské pohlaví; Cytochrome P-450 CYP3A; plocha pod křivkou; Child, Preschool; protein spojený s mnohočetnou rezistencí k lékům 2; Alleles; Adolescent; Area Under Curve; časové faktory; frekvence genu; kyselina mykofenolová; ženské pohlaví; Dose-Response Relationship, Drug; Female; Multidrug Resistance-Associated Protein 2; vztah mezi dávkou a účinkem léčiva; jednonukleotidový polymorfismus; genotyp; lidé; Immunosuppressive Agents; mladiství; Polymorphism, Single Nucleotide; dítě; Child; Male; cytochrom P-450 CYP3A